Balancing shipping and protection of the marine environment: A study of the proposed designation of the Straits of Malacca and Singapore as a particularly sensitive sea area - Mohd Rusli, Mohd Hazmi (2011)
The Straits of Malacca and Singapore are two of the most important shipping passages in the world, accommodating approximately 80,000 vessel movements per year.The Straits of Malacca and Singapore fulfill the character of straits used for international navigation under the 1982 United Nations Convention on the Law of the Sea (LOSC). The transit passage regime as described in Part III of the LOSC is the navigational regime that applies to all ships that transit the Straits.Under this regime, the littoral States have limited powers to regulate shipping and they can only employ environmental protective measures by giving effect to applicable international regulations.With the steady increase of shipping traffic each year, it is becoming more difficult for the littoral States to manage the well-being of the marine environment of the Straits.Heavy shipping does bring adverse effects to the marine environment of the Straits of Malacca and Singapore.This study aims to look at the possibility and feasibility of the Straits of Malacca and Singapore being designated as a Particularly Sensitive Sea Area (PSSA).Following such a designation, as PSSA is not a stand-alone measure, this article concludes by suggesting the most appropriate associated protective measure (APM) to be imposed in the Straits of Malacca and Singapore.The Straits of Malacca and Singapore are located in one of the world’s recognised ‘mega biodiversity’ regions, and therefore it is crucial to protect and preserve the marine environment of these Straits from unwarranted degradation.